Investigating the psychometric characteristics of nurses' care behaviours scale in Turkish culture - Ozcan, Serpil; Bahcecioglu Turan, Gulcan; Sarialioglu, Arzu; Ciftci, Bahar (Bmc, 2026)
Objective The cultural characteristics of care behaviors in Turkish healthcare services underscore the need for a culturally adapted measurement tool to reliably assess these behaviors. This study investigated the validity and reliability of the Nurses' Care Behaviors Scale for evaluating care provided to patients in accordance with Turkish standards. Methods This cross-sectional psychometric validity study was conducted between January 2024 and December 2024, involving 320 patients receiving inpatient treatment in the internal medicine and surgical units of a tertiary university hospital in eastern Turkey. Data were collected face-to-face using the Personal Information Form and the Nurses' Care Behaviors Scale. Measurement invariance was assessed using Multigroup Confirmatory Factor Analysis across age, gender, and marital status to ensure the scale's equivalence across demographic groups. Results The scale had a Content Validity Index of 0.97, an item factor load range of 0.779 to 0.901, and a Cronbach's Alpha value of 0.976. The CFI showed that the 14-item, one-dimensional Nurses' Care Behaviors Scale was still the same in its Turkish form; no changes were made to the original scale form, and good fit index values were found. Multigroup CFA supported full configural, metric, scalar, and strict invariance across all demographic subgroups. Conclusion The Turkish version of the Nurses' Care Behaviors Scale is a valid and reliable measurement tool to evaluate nurses' care behaviors and can be confidently used in clinical practice across different demographic groups.
Keywords: Validity; Reliability; Nurse; Care behaviors scale